Student manual for theory and practice of group counseling - Corey, Gerald (California : Brooks/Cole Publishing Company, 1995)
Designed to help students create their own theory and style of group leadership, this manual includes concepts to think about, material to experiment with, and activities students can do on their own. The Student Manual includes self-inventories to assess attitudes, ideas for role playing, techniques for group interaction, practical problems that occur in groups, group exercise for experiential practice, summary tables that show stages of groups for each of the theories, questions for discussion and reflection, and test questions to assess comprehension.
Keywords: Group counseling; Small groups